Studies on Degradability of High Density Polyethylene (HDPE)–Polylactide (PLA) Blends - Madhu, Gaurav (My University, 2015)
Polyethylene (PE) is predominantly used for consumer packaging in the form of trash bags and other short-term flexible packaging and disposable products because they are economical and convenient. But, due to non-biodegradable nature, they cause hazardous environmental pollution and become carcinogenic for human beings, marine bodies and other living species. Hence, the major challenges and opportunities exist in developing biodegradable polyethylene blends having similar mechanical and processing properties as that of the conventional PE. The objectives of this research work were set to develop biodegradable and oxo-biodegradable blends of high-density polyethylene (HDPE) by compounding poly(lactic acid) (PLA) in varying amounts and/or pro-oxidant with/without compatibilizer maleic anhydride grafted high density polyethylene (MA-g-HDPE), to investigate the effect of blend composition on the performance properties and degradability and to study degradation kinetics of the polymer blends. The selection of HDPE was made due to its large use in current commercial packaging. PLA is a well known biodegradable polyester polymer having good mechanical properties, fair processability and superior recyclability; hence, emerging as a viable substitute for synthetic, semi-crystalline non-biodegradable polymers. MA-g-HDPE was selected as compatibilizer due to the intrinsic immiscibility between HDPE and PLA. Thin films from HDPE/PLA blends were produced through melt-compounding followed by hot-pressing. Initially, the ratios of HDPE/PLA blends were taken as 100/0, 95/5, 90/10, 85/15, 80/20, 75/25, and 70/30 and after recognizing 80/20 blend with optimum combination of mechanical (tensile) properties and PLA content, it was further compatibilized with 2, 4, 6, and 8 parts per hundred of resin (phr) of MA-g-HDPE. Amongst compatibilized HDPE/PLA (80/20) blends, 4 phr quantity of MA-g-HDPE blends had the finest relevant mechanical properties. Subsequently, neat HDPE and selected HDPE/PLA blends were formulated with an ever-effective pro-oxidant additive cobalt stearate (CoSt) to influence the initial rates of degradation. The characterization of the selected films was done by a number of techniques including Fourier transform infrared spectroscopy (FTIR), wide angle X-ray diffraction (WAXD), thermogravimetric analysis (TGA) differential scanning calorimetry (DSC), scanning electron microscopy (SEM), and parallel-plate rheometry. Considering the importance of permeability or barrier properties for packaging of fresh produce, water vapour transmission rate (WVTR) of the optimized blend films was also determined. Further, biodegradation in terms of CO2 gas produced by the samples (in grams) and percent mineralization was analyzed under composting conditions according to ASTM D5338 standard. An economical apparatus for measuring biodegradation was developed indigenously as per the guidelines of the ASTM standard which gave consistent and reliable results on the biodegradability of the samples. Thermal degradation kinetics and lifetime of HDPE/PLA blends were assessed by using TGA data and applying the well known isoconversional methods viz. Friedman, Kissinger and Flynn–Wall. FTIR of 80/20 blend with compatibilizer represented different peak positions of carbonyl stretching band indicating promotion of some compatibility between the two immiscible polymers. Thermal investigation (TGA and DSC) revealed that the thermal stability of HDPE decreased with addition of PLA but still, the blends were stable enough to be used for packaging application(s). WAXD analysis revealed lesser crystallinity of the blends than pure HDPE. Through SEM, it was observed that MA-g-HDPE influenced the morphology of the blends and it acted as a suitable compatibilizer for HDPE/PLA blends. Rheology of the samples confirmed that the blends retain their processability as they were pseudoplastic in nature. WVTR of the optimized HDPE/PLA blends met the specified standard value for packaging applications. The biodegradability levels of the samples under composting environment were obtained as cellulose (43.2%) ˃ HD80MA4CoSt0.1 (10%) > HD80CoSt0.1 (9.1%) > HD80MA4 (3.7%) > HD80 (3.5%), which suggested that the blends containing pro-oxidant were more degraded. The effect of pro-oxidant on the thermal degradation kinetics and lifetime of HDPE and HDPE/PLA blended films was observed using thermogravimetry and applying the isoconversional techniques mentioned above. It was observed that CoSt provoked the thermal degradation and biodegradation of HDPE and HDPE/PLLA blends and decreased their lifetime as well.
PHD, CHED
Keywords: HDPE; PLA; Blends; Degradability; CHED